The players - Arthur Andersen & Co. (Marietta, GA : Longstreet, 1999)
"Interviews conducted for the 'The Players' segment of the Arthur Andersen-sponsored CNN program Business Unusual, 30 global leaders share their own definitions of decision-making, strategy and success."--Page [2].